Structural characterization and effect on anti-angiogenic activity of a fucoidan from Sargassum fusiforme. (20th January 2016) - Cong, Qifei; Chen, Huanjun; Liao, Wenfeng; Xiao, Fei; Wang, Peipei; Qin, Yi; Dong, Qun; Ding, Kan
Highlights: A fucoidan from Sargassum fusiforme was isolated and characterized. Backbone was alternate 1, 2-linked α-d -Man p and 1, 4-linked β-d -Glc p A. Branches contain fucose, xylose, galactose, glucuronic acid and sulfate group. Fucoidan could significantly inhibit the tube formation. Oligosaccharide fractions exhibited the anti-angiogenesis activities. Abstract: A fucoidan FP08S2 was isolated from the boiling-water extract of Sargassum fusiforme, purified by CaCl2 precipitation and chromatography on DEAE-cellulose and Sephacryl S-300. FP08S2 contained fucose, xylose, galactose, mannose, glucuronic acid, and 20.8% sulfate. The sulfate groups were attached to diverse positions of fucose, xylose, mannose, and galactose residues. The backbone of FP08S2 consisted of alternate 1, 2-linked α-d -Man p and 1, 4-linked β-d -Glc p A. Sugar composition analysis and ESI-MS revealed that the oligosaccharides from branches contained fucose, xylose, galactose, glucuronic acid and sulfate. FP08S2 could significantly inhibit tube formation and migration of human microvascular endothelial cells (HMEC-1) dose-dependently. These results suggested that the fucoidan FP08S2 from brown seaweeds S. fusiforme could be a potent anti-angiogenic agent.